ESG Disclosure, Intellectual Capital, and Firm Value in the Energy Sector in Indonesia: The Moderating Role of Firm Size - Maysari, Maysari; Endri, Endri (International Journal of Energy Economics and Policy, 2025)
This study aims to analyze the impact of Environmental, Social, and Governance (ESG) disclosure, Intellectual Capital (IC), and capital structure proxied by Debt to Equity Ratio (DER) on Firm Value (FV), with Firm Size (FS) as a moderating variable, in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. Using a panel data regression method on 31 companies, this study found that ESG disclosure had a positive and significant effect on FV. However, IC did not show a positive impact on FV, even tending to be negative in Model 1, indicating that the market has not fully valued this intangible asset in the energy sector. Meanwhile, DER showed contradictory results (positive in Model 1, negative in Model 2), reflecting sensitivity to model specifications. FS itself had a negative and significant effect on FV, implying diseconomies of scale or agency problems in large companies. The important moderating role of FS is evident in its adverse moderating impact on the relationship between ESG and FV, where larger firms are less effective in translating ESG disclosure into higher value. Conversely, FS positively moderates the relationship between DER and FV, indicating that larger firms utilize debt more optimally. However, FS does not moderate the relationship between IC and FV. This research provides critical insights for investors and management of energy sector companies, particularly in addressing the complex relationship between sustainability practices, intangible assets, financing structures, and market value amid the global energy transition.